Effect of lockdown due to COVID-19 pandemic on lipid profile of Indian male population - Tripathy, Subrat K.; Ray, Subhashree (International Journal of Scientific Reports, 2021)
Background: SARS-COV-2 pandemic is one of the biggest health challenges for modern era and this type of pandemic was never witnessed in recent past. To control the pandemic various measures were taken by various authorities like lockdown and shutdown. This study was meant to find the effect of this new way of social isolation during lockdown on Indian male population. Methods: The study was conducted in IMS and SUM hospital, Bhubaneswar, Odisha. Those having routine blood check-up before lockdown in the hospital were again re-evaluated for their lipid profile after lockdown. Only male between age group of 20 to 59 included in the study who were mostly confined to home during lockdown. Female, front line workers and people already having deranged lipid profile were excluded from the study. Results: It was found that there are significant variations in the triglyceride and cholesterol level in men before and after lockdown whereas the level of HDL did not show any significant variation. Conclusions: From above study it may be concluded that though lockdown is somehow able to control the rapid spread of the virus but it has negative effect on the lipid profile and indirectly cardiovascular health of a man.